Magnetic Conjugated Polymer Nanoparticles with Tunable Wettability for Versatile Photocatalysis under Visible Light - Bayarkhuu, Bolormaa; Yang, Can; Wang, Wenyan; Zhang, Kai A., I; Byun, Jeehye (AMER CHEMICAL SOC, 2020)
Limited dispersibility of conjugated polymer photocatalysts in solvents narrows the options of exploring for diverse photocatalytic reactions. In this study, we report magnetic conjugated polymer nanoparticles made of conjugated polyelectrolytes, which exhibited tunable wettability in solvents. The dispersibility of photocatalysts could be altered by the exchange of anions on the nanoparticles, which thereby covers a wide range of solvents from water to toluene. The optimized wettability of the photocatalysts in desired solvents was demonstrated by two model reactions under visible light irradiation, namely, photodegradation of tetracycline in water and photooxidative coupling of benzylamines in acetonitrile. The magnetic conjugated polymer nanoparticles could be easily regenerated from the reaction solvents via the magnetic separation technique.
Keywords: IN-SITU SYNTHESIS; TETRACYCLINE; WATER; REMOVAL; ANTIBIOTICS; COMPOSITES; CATALYSIS